Temporal trends and patterns in antimicrobial-resistant Gram-negative bacteria implicated in intensive care unit-acquired infections: A cohort-based surveillance study in Istanbul, Turkey. (September 2018) - Durdu, Bulent; Kritsotakis, Evangelos I.; Lee, Andrew C.K.; Torun, Perihan; Hakyemez, Ismail N.; Gultepe, Bilge; Aslan, Turan
Highlights: Surveillance of Gram-negative bacterial infections in intensive care patients in Istanbul. Overall infection rate substantially and progressively decreased over 4 years. Antimicrobial resistance patterns varied markedly by organism and time. A back-to-susceptibility trend was noted for Pseudomonas aeruginosa . Extensively drug-resistant proportions remained constant in Klebsiella spp. but increased in Acinetobacter baumannii . Abstract: Objectives: This study assessed trends and patterns in antimicrobial-resistant intensive care unit (ICU)-acquired infections caused by Gram-negative bacteria (GNB) in Istanbul, Turkey. Methods: Bacterial culture and antimicrobial susceptibility data were collected for all GNB causing nosocomial infections in five adult ICUs of a large university hospital in 2012–2015. Multiresistance patterns were categorised as multidrug-resistant (MDR), extensively drug-resistant (XDR) and pandrug-resistant (PDR). Temporal patterns and trends were assessed using regression analyses. Results: Of 991 pathogenic GNB recorded, the most frequent were Acinetobacter baumannii (35.3%), Klebsiella spp. (26.7%), Pseudomonas aeruginosa (18.1%) and Escherichia coli (6.7%). The overall infection rate decreased by 41% from 18.4 to 10.9 cases per 1000 patient-days in 2012 compared with 2015 ( P <  0.001), mostly representing decreases in bloodstream infections and pneumonias by A. baumannii and P. aeruginosa . The XDR proportion in A. baumannii increased from 52.4% in 2012 to 71.7% in 2015, but only one isolate was colistin-resistant. Multiresistance patterns remained stable in Klebsiella, with overall XDR and possible PDR proportions of 14.3% and 1.9%, respectively. A back-to-susceptibility trend was noted for P. aeruginosa in which the non-MDR proportion increased from 53.3% in 2012 to 70.6% in 2015. Moreover, 87.9% of E. coli and 39.5% of Enterobacter isolates were MDR, but none was XDR. Conclusions: Antimicrobial resistance patterns in pathogenic GNB continuously change over time and may not reflect single-agent resistance trends. The proportionate amount of antimicrobial-resistant GNB may persist despite overall decreasing infection rates. Timely regional surveillance data are thus imperative for optimal infection control.